Solar-hydrogen Production by a Monolithic Photovoltaic-electrolytic Cell - Jeon, Hyo Sang; Min, Byoung Koun (KOREAN ELECTROCHEMISTRY SOC, 2012)
Among the various solar-hydrogen production techniques a combination of a photovoltaic (PV) and an electrolytic cell into one single system, a monolithic PV-electrolytic cell, has been suggested as a promising one in terms of efficiency and stability. In this mini-review, we describe our recent efforts on the fabrication of the monolithic PV-electrolytic cell. Particularly, we focus on the electrocatalysts for water oxidation and its fabrication method suitable for a monolithic PV-electrolytic cell. We also introduce proto-type devices with a dye-sensitized solar cell module and an InGaP/GaAs photoelectrodes.